Phosphorous availability in Argisols and suffi ciency range in sugarcane in the Northeast of Brazil - Batista da Costa, Daniela; José Freire, Fernando; de Oliveira Lemos, Janyelle; Roberta Vasconcelos da Silva, Suellen; Sobral Bezerra, Nathalia; Karla Batista de Andrade, Patrícia; Andrade, Joel (Revista Ciência Agronômica, 2023)
Phosphorous is a limiting nutrient in sugarcane cultivated in Argisols in the Northeast of Brazil, and understanding itsavailability in the soil, as well as determining suffi ciency ranges in the plants is essential when recommending levels of phosphorusfertiliser. The aim of this study was to: (i) Defi ne class es for interpreting P availability in Argisols of the Northeast using the Mehlich-1and Anion Exchange Resin (AER) extractors; (ii) Evaluate P extraction by the same extractors; and (iii) Correlate the P content of thesoil with the P content of the plants, and establish suffi ciency ranges in the plants. Three fi eld trials were carried out in a sandy (PVAd1),medium (PAdx) and clayey (PVAd2) Argisol, applying the following amounts of P: 0, 40, 80, 120, 160 and 200 kg ha-1 P2O5. The AERextracted more P than did Mehlich-1 from each of the soils. The P content of the classes for interpreting P availability determined bythe AER were higher than those determined by Mehlich-1. AER was the best extractor to represent P availability in the Argisol withthe clayey texture (PVAd2), and Mehlich-1 in the Argisol with the sandy texture (PVAd1). The ranges of P suffi ciency in the leaves ofthe sugarcane varied between soils, with values of 0.66-0.73 g kg-1 in PVAd1, 0.59-0.69 g kg-1 in PVAd2 and 0.34-0.47 g kg-1 in PAdx.As such, the texture of Argisols cultivated with sugarcane in the Northeast of Brazil should be a criterion for choosing the Pextractor used in assessing its availability.